Phosphoinositides and the Fate of Legionella in Phagocytes - Swart, A. Leoni; Hilbi, Hubert (Frontiers in Immunology, 2020)
Legionella pneumophila is the causative agent of a severe pneumonia called Legionnaires’ disease. The environmental bacterium replicates in free-living amoebae as well as in lung macrophages in a distinct compartment, the Legionella-containing vacuole (LCV). The LCV communicates with a number of cellular vesicle trafficking pathways and is formed by a plethora of secreted bacterial effector proteins, which target host cell proteins and lipids. Phosphoinositide (PI) lipids are pivotal determinants of organelle identity, membrane dynamics and vesicle trafficking. Accordingly, eukaryotic cells tightly regulate the production, turnover, interconversion and localization of PI lipids. L. pneumophila modulates the PI pattern in infected cells for its own benefit by (i) recruiting PI-decorated vesicles, (ii) producing effectors acting as PI interactors, phosphatases, kinases or phospholipases, and (iii) subverting host PI metabolizing enzymes. The PI conversion from PtdIns(3)P to PtdIns(4)P represents a decisive step during LCV maturation. In this review, we summarize recent progress on elucidating the strategies, by which L. pneumophila subverts host PI lipids to promote LCV formation and intracellular replication.